2020
DOI: 10.1038/s41598-020-71686-4
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling source of moisture driving glacier dynamics and identification of 8.2 ka event: evidence from pore water isotopes, Western Himalaya

Abstract: Two atmospheric circulation patterns, the Indian Summer Monsoon (ISM) and mid-latitude Westerlies control precipitation and thus glacier variability in the Himalaya. However, the role of the ISM and westerlies in controlling climate and thus past glacier variability in the Himalaya is poorly understood because of the paucity of the ice core records. In this article, we present a new Holocene paleorecord disentangling the presence of the ISM and mid-latitude westerlies and their effect on glacier fluctuations d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 64 publications
2
6
0
Order By: Relevance
“…Thus, we have pointed out two additional classes of exact solutions ( 12)-( 13) of Eqns. ( 1)-( 2) in their approximation (11) for creeping flow of glacial ice, which differ from solutions (10) for stationary approximation creeping flow of glacial ice with constant pressure field along the path of the plane-parallel flow of glacial ice. Videlicet, 1st class is also associated with stationary flow (but variable pressure field), the 2nd stems from assumption of constant pressure field along the path of the plane-parallel flow, but we have considered nonstationary case of glacial ice in this case.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Thus, we have pointed out two additional classes of exact solutions ( 12)-( 13) of Eqns. ( 1)-( 2) in their approximation (11) for creeping flow of glacial ice, which differ from solutions (10) for stationary approximation creeping flow of glacial ice with constant pressure field along the path of the plane-parallel flow of glacial ice. Videlicet, 1st class is also associated with stationary flow (but variable pressure field), the 2nd stems from assumption of constant pressure field along the path of the plane-parallel flow, but we have considered nonstationary case of glacial ice in this case.…”
Section: Discussionmentioning
confidence: 84%
“…But since at this stage algorithm for further obtaining of exact solution has no chance to be presented in analytical or semi-analytical way, we should apply additional simplifications to equations of system (11)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid centennial climate changes, mainly occurred at 10.7‐9.5, 8.7‐8.5, 7.7‐7.4, 6.4‐6, 5.5‐5.2, 4.8‐4.5, 4‐3.6, 3.1‐2.7, 1.4‐1.2, and 0.8‐0.6 cal kyr BP, had also been recorded by rapid retreat of coniferous forest in peat deposits from Zoige Basin (Sun et al., 2017). Several other sediment archives including the δ 18 O values from Guliya ice core (Thompson et al., 1997), δ 18 O ost results from Lake Koucha (Mischke et al., 2008), δ 13 C values of cellulose remains from Hongyuan peat (Hong et al., 2003), pollen records from Lake Qinghai (Shen et al., 2005) as well as porewater δ 18 O values from Lake Chandratal (Kumar et al., 2020) have also suggested similar centennial climate fluctuations. A synthesis of all those records reveals that the climatic conditions on the TP might have been highly unstable throughout the Holocene.…”
Section: Discussionmentioning
confidence: 99%
“…Note the close correlation between those climate events and the Ice-rafted events in the North Atlantic. Lake Koucha (Mischke et al, 2008), δ 13 C values of cellulose remains from Hongyuan peat (Hong et al, 2003), pollen records from Lake Qinghai (Shen et al, 2005) as well as porewater δ 18 O values from Lake Chandratal (Kumar et al, 2020) have also suggested similar centennial climate fluctuations. A synthesis of all those records reveals that the climatic conditions on the TP might have been highly unstable throughout the Holocene.…”
Section: Centennial-scale Climate Fluctuations On Northeastern Tp Dur...mentioning
confidence: 92%